Exploring gender- and nutrition-sensitive climate-smart agriculture value chains for Nwoya District, Northern Uganda - Bamanyaki, Patricia A.; Muchunguzi, Perez (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Recent statistics indicate a rise in food security among Uganda’s population over the period 2014 to 2019. Gender- and nutrition-sensitive agriculture may improve food and nutrition insecurity by sustainably addressing underlying causes of malnutrition. The Climate Risk Profiling Methodology is useful in assisting district-level agricultural development practitioners in identifying and prioritizing gender-sensitive value chain enterprise options with the potential to improve household incomes, food and nutrition security. Four value chain enterprises that may be promoted based on economic importance, resilience to climate change, gender sensitivity and importance for food and nutrition security are cassava, poultry, goats and beans. Considerations for policy action to improve food and nutrition security in Nwoya District amidst climate change include: boosting local production of diverse nutrient-dense foods; enhancing sustainable agricultural productivity and incomes; social behavior change; communication focusing on nutrition; providing supportive institutions, infrastructure and services; and the use of gender transformative approaches to boost women’s effective participation, agency and benefit from agricultural value chain enterprises.